Hyperhomocysteinemia in a Patient with Moyamoya Disease - Durga Shankar Meena; Gopal Krishana Bohra; Mahadev Meena; Bharat Kumar Maheshwari (Case Reports in Neurological Medicine)
Moyamoya disease is a chronic progressive cerebrovascular disease characterized by bilateral occlusion or stenosis of arteries around circle of Willis. We report a case of 18-year-old female presented with recurrent episodes of headache and vertigo. On cerebral angiography, the patient was diagnosed to have moyamoya disease. On further evaluation, thrombophilia profile showed increased homocysteine level. The patient was treated conservatively with cobalamin and aspirin and advised for revascularization. According to the literature, there are few case reports of moyamoya disease with thrombotic disorders. Hence, we are reporting this interesting and rare case.